Japanese Directive Speech - Kadek Widari; Ni Luh Yaniasti (International Journal of Multidisciplinary Sciences, 2023)
Language in role as a means of communication could result in relationships between speakers of to said. The use of language in the process of communication is very important, because community life is made possible by speech. Speechs are used to information of ideas, intentions directly or indirectly. Speech act serves to declare mean it is speakers by speech partners of said. Directive speech is the type of a speech that used by speakers of to send the speech partner said do something. The use of directive speech in conveying a speech should look factors affecting the speech. The porpuse in this research was to identify the directive speech acts and factors that affect the level of politeness. The method in this research used qualitative method with descriptive analysis method. The theory in this research used were speech act theory by Yule and politeness theory by Mizutani. The results of the analysis, the forms of directive speech acts contained in the comic Ore wo Suki Nano wa Omae dake kayo are 1) directive speech acts of command marked by tamae and nasai, 2) directive speech acts of requests marked by te kure, naide kure, te kudasai, tte, te, and te hoshii; 3) the directive speech act of an invitation is marked with mashou; 4) directive speech acts of permission marked by te mo ii and 5) directive speech acts of suggestions marked with houga ii. Directive speech is influenced by several factors, namely: 1) familiarity factor; 2) age; 3) social relationship; 4) gender and 5) situation.